Synthesis, characterization and performance of Ni/mesoporous silica - NH\(_2\)/mesoporous silica and Ni-NH\(_2\)/mesoporous silica as bifunctional catalyst in one step conversion of waste palm oil to biodiesel - Fitria, Anissa; Trisunaryanti, Wega; Triyono; Santoso, Iman (Communications in Science and Technology, 2024)
Sidoarjo mud is a natural material resulted from an unusual natural phenomenon and is rich in silica contents. So far, no studies have been reported about mesoporous silica from Sidoarjo Mud, which is a supported catalyst for one-step conversion to biodiesel. This study aims to explore synthesis, characterization, and applications to demonstrate the heightened activity and selectivity in the esterification- transesterification of waste palm oil into biodiesel, utilizing a one-step method aligned with the principles of green chemistry using two bifunctional catalysts (Ni/MS - NH2/MS and Ni-NH2/MS). The bifunctional catalysts were prepared by means of hydrothermal, wet impregnation, and grafting methods. The highest biodiesel yield (78.77%) was achieved under the condition of 65 °C, 3 h, methanol to oil ratio 21 : 1, and 3wt% of Ni/MS - NH2/MS as the catalyst. The catalyst was able to yield a conversion level as good as ~72% in the 3rd cycle after regeneration. The research demonstrates the industrial relevance of the catalyst, offering a sustainable solution for biodiesel production and waste management.